Insular Cortical Projections to Functional Regions of the Striatum Correlate with Cortical Cytoarchitectonic Organization in the Primate - Chikama, Masanori (J Neurosci, 1997)
We examined the striatal projections from different cytoarchitectonic regions of the insular cortex using anterograde and retrograde techniques. The shell and medial ventral striatum receive inputs primarily from the agranular and ventral dysgranular insula. The central ventral striatum receives inputs primarily from the dorsal agranular and dysgranular insula. Projections to the central ventral striatum originate from more posterior and dorsal insular regions than projections to the medial ventral striatum. The dorsolateral striatum receives projections primarily from the dorsal dysgranular and granular insula. These results show that cytoarchitectonically less differentiated (agranular) insular regions project to the ventromedial “limbic” part of the ventral striatum, whereas more differentiated (granular) insular regions project to the dorsolateral “sensorimotor” part of the striatum. The finding that the ventral “limbic” striatum receives inputs from less differentiated regions of the insula is consistent with the general principle that less differentiated cortical regions project primarily to the “limbic” striatum. Functionally, the ventral striatum receives insular projections primarily related to integrating feeding behavior with rewards and memory, whereas the dorsolateral striatum receives insular inputs related to the somatosensation. Information regarding food acquisition in the insula may be sent to the intermediate area of the striatum.